Bilingual Omnichannel Contact Center with 4.0 technology at Sena CBI Palmira? - Cardenas Acevedo, Lilian Patricia
This project seeks for the CBI to increase a technological infrastructure for professional training in bilingual BPO and thereby satisfy the needs that exist in the BPO sector, mainly in the commerce and service part. This is how the doors to the project "Update of comprehensive training environment Bilingual Omnichannel Contact Center BPO shared services model with 4.0 technology" are opened.  For this reason, implementing in the CBI a technological infrastructure for professional training in both BPO and industry 4.0 and bilingualism would support the needs that the market currently has; This is how this project was born, a Bilingual Omnichannel Contact Center comprehensive training environment, which will be a shared services model uniting BPOs with 4.0 technology. This would set a trend, given that increasing the use of technologies combined with Industries 4.0, bilingualism and BPOs, will allow the digitization of companies, guaranteeing customer satisfaction and generating new jobs in the BPO sector. This model will be implemented through an environment of training that simulates a Contact Center, with the aim of strengthening the skills of apprentices relating BPOs with 4.0 technology, which responds to market needs.